Crab fishery of t h e Calicut coast with some aspects of t he population characteristics of Portunus sanguinolentus, P. pelagicus and Charybdis cruciata - Sarada, P T (Indian Journal of Fisheries, 2011)
Annual crab landings by mechanised trawlers ranged between 9.0 t (1988-'89)and 64.0 t (1987-'88). During 1987-'91 period. Portunus sanguinolentus (94.2%), P. pelagicus (3.0 %) and Charybdis cruciata (2.8 %) were the dominantspecies. The carapace length-body weight relationship were : W = 0.01037 L^^"'for P. sanguinolentus, W = 0.00374 L = ^^'^ •' for P. pelagicus and W= 0.00059L ^^^'•'' for C. cruciata. The carapace width-body weight relationships of therespective species were : W = 0.00013 L ''•^"^^ W = 0.00024 U™" and W =0.00029 L ^ "'"*''. The carapace length-carapace width relationships were W =19.636+1.7218 L for P. Sanguinolentus, W = 13.6133 + 1. 9549 L for P.pelagicus and W = 0.9874 + 1. 5473 L for C. Cruciata. The size varied from26-175 mm carapace with (C W) in P. sanguinolentus, 66-115 mm C W in P.pelagicus and 51-120 mm C W in C cruciata. In P. sanguinolentus a regularpattern of dominance of one sex over the other was absent. Maturity studyindicated spawning throughout the year and the size at first maturity in femalewas 82.99 mm C.W. The L , K (annual) and t^ (annual) values were 172.9 mmC.W., 1.4939 and -0.0482 respectively in male. The respective values in femalewere 161.8 mm C.W., 1.574 and -0.0635.Introduction (